Effectiveness Of Green Nanochitosaan Addition On Compressive Strength Of Glass Ionomer Cement - Rahma Wadania Lobubun; Noor Hafida Widyastuti; Nur Ariska Nugrahani; Edi Karyadi (Jurnal EduHealth, 2023)
Glass ionomer cement is a restorative material that is adhesive, tooth-colored, and has the ability to release fluoride ions which are affected by the degree of acidity (pH). Apart from that, one way to utilize the waste from green mussels is by processing them into chitin and chitosan as materials to strengthen the properties of glass ionomer cement. Glass ionomer cement contains materials such as powderacid soluable calcium fluoraluminosilicate glass and liquidaqueous solution of polyacrylic acid. This can be an alternative as a treatment for dental caries. Objective: This study aims to determine the effectiveness of the addition of green mussel shell (perna viridis) nanochitosan on the compressive strength of glass ionomer cement. Method: This study used a quantitative experimental laboratory study with a True Experimental study design using a post test only control group design. the total sample used was 25 samples. Results: The 2% nanochitosan concentration has the highest compressive strength value compared to other concentrations, as evidenced by the mean value at 2% concentration, which is 4.10 MPa. Conclusion: The result of 2% green mussel (perna viridis) nanochitosan was the most effective treatment in influencing the compressive strength of glass ionomer cement. The greater the concentration used, the higher the compressive strength of the resulting glass ionomer cement.